2018
DOI: 10.17223/15617793/430/20
|View full text |Cite
|
Sign up to set email alerts
|

On the Application of the Mechanism for Implementing the New Educational Standard in Integration With the Developed Professional Standards

Abstract: Статья посвящена изучению изменений процесса проектирования естественнонаучной и профессиональной подготовки обучающихся организаций профессионального образования в условиях интеграции новых образовательных и профессиональных стандартов. Представлены данные опроса преподавателей колледжей Центрального и Южного федеральных округов в условиях внедрения образовательного стандарта четвертого поколения и профессиональных стандартов по направлениям подготовки, объединяющим профессии и специальности. Ключевые слова: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The research of Kamaleeva (2018) has shown that even in the region with a rather high level of economic development the interested part of teachers has come to an understanding that natural-science and vocational training of students has to meet the requirements of modern labour market according to the requirements of the developed professional standard. The analysis of professional activities which the Bachelor students of most engineering majors in Russia are prepared for allowed to identify that the main of them are design-and-engineering, production-and-technological, management and scientific-andresearch activities.…”
mentioning
confidence: 99%
“…The research of Kamaleeva (2018) has shown that even in the region with a rather high level of economic development the interested part of teachers has come to an understanding that natural-science and vocational training of students has to meet the requirements of modern labour market according to the requirements of the developed professional standard. The analysis of professional activities which the Bachelor students of most engineering majors in Russia are prepared for allowed to identify that the main of them are design-and-engineering, production-and-technological, management and scientific-andresearch activities.…”
mentioning
confidence: 99%